Who struggles to decide? Personality, gender, and career indecision in higher education - Alotaibi, Turkiah; Almusharraf, Norah; Jasser, Maha (Frontiers in Education, 2025)
IntroductionCareer indecision slows progress through university and into work, yet evidence from Middle Eastern settings remains limited.MethodsWe surveyed 153 Saudi undergraduates across seven programmes and modelled a 12-item Career Decision-Making Difficulties composite against gender, Big Five traits (extraversion, openness, conscientiousness), and educational cohort (first vs final year).ResultsGender showed no association with indecision. In multiple regression, extraversion was positively related to indecision, openness showed a non-significant negative trend, and conscientiousness showed no reliable effect; overall explained variance was small (R2 = 0.075). First-year and final-year students did not differ significantly.DiscussionThese results indicate that binary gender contrasts add little explanatory power in this context, that approach-oriented traits offer only modest leverage when indecision is treated as a single composite, and that year of study does not, on its own, account for uncertainty. Future work in the region should move beyond composites toward domain-specific difficulty profiles and longitudinal designs to capture change over time.